Determinant of Capital Structure and Earning Quality: Evidence from Indonesian Listed Commercial Banks, 2008–2024 - Yudih, Sudirman (Universitas Islam Negeri Alauddin Makassar, 2025)
This study investigates the determinants of capital structure and their implications for earnings quality in Indonesian listed commercial banks. Using panel data from eight banks on the Indonesia Stock Exchange (2008–2024) and applying Structural Equation Modeling (SEM), the research analyzes the direct and indirect effects of firm size and earnings management on capital structure and earnings quality. The results show that firm size does not significantly affect capital structure, indicating that larger banks tend to prioritize internal funding over external debt. In contrast, earnings management exerts a significant positive influence on capital structure, suggesting its relevance in shaping financing decisions. However, earnings management does not directly enhance earnings quality, reflecting the influence of regulatory oversight and governance frameworks in limiting discretionary reporting practices. Capital structure is identified as the strongest determinant of earnings quality, demonstrating a substantial positive effect while also mediating the relationships among firm size, earnings management, and earnings quality. These findings underscore the importance of maintaining balanced leverage to strengthen financial discipline, monitoring mechanisms, and reporting credibility. The study contributes sector-specific evidence from an emerging market and provides practical insights for banking practitioners, regulators, and investors regarding financial strategy, governance, and transparency